Barriers to Social Enterprise Growth1. (6th March 2018) - Davies, Iain Andrew; Haugh, Helen; Chambers, Liudmila
Abstract : This study investigates barriers to social enterprise growth. The research employs qualitative case study data gathered from young social enterprises to examine the interplay between social enterprise and individual, organizational and institutional barriers to growth. We find that social enterprise barriers to growth are based on values differences, business models, and institutional norms. We theorize three strategic responses to overcome barriers to growth: values‐based decision‐making, leveraging social mission, and anchoring.